2004
DOI: 10.2190/ax2d-y9vm-v7px-0tad
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulated Learning in Web-Based Environments: Instructional Tools Designed to Facilitate Cognitive Strategy Use, Metacognitive Processing, and Motivational Beliefs

Abstract: This study investigated strategies teachers can use to improve students' use of self-regulated learning strategies in a Web-based setting. SRL is defined as a learner's intentional efforts to manage and direct complex learning activities and is composed of three primary components including cognitive strategy use, metacognitive processing, and motivational beliefs. These three components are defined relative to note-taking methods (cognitive component), self-monitoring prompts (metacognitive component), and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
128
0
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(140 citation statements)
references
References 50 publications
3
128
0
9
Order By: Relevance
“…Based on literature, students' discipline act as moderator variable in students' perceptions of learning environment, motivation to learn, and using learning strategies (Cleary & Chen, 2009;Crede & Philips 2012;Judd, 2009;Ghosh2011;Kauffman, 2004;Artino, 2009). Therefore, the level of students' motivation and learning strategies are possible to be somewhat different for various classes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on literature, students' discipline act as moderator variable in students' perceptions of learning environment, motivation to learn, and using learning strategies (Cleary & Chen, 2009;Crede & Philips 2012;Judd, 2009;Ghosh2011;Kauffman, 2004;Artino, 2009). Therefore, the level of students' motivation and learning strategies are possible to be somewhat different for various classes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it can lack the direct and personal supervision of the instructor, which might result in learner's sense of isolation and an accompanying lack of engagement (Barak et al, 2016). Studies on the use of advanced technologies indicated that the application of self-regulatory strategies might facilitate the use of cognitive strategies, metacognitive processing, and motivational beliefs (Cho & Heron, 2015;Kauffman, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, such methods include metacognitive cueing [60], reflective prompting [13], questioning [29,30], self-generated inferences [63]; self-monitoring or reflection [27], and self-explanations [10]. Many of these strategies can be grouped within the broader category of metacognitive prompting, which [25] define as ''an externally generated stimulus that activates reflective cognition or evokes strategy use with the objective of enhancing learning'' (p. 878).…”
Section: Introductionmentioning
confidence: 99%